The Effect of Accounting Information Systems and Internal Control Systems on the Quality of Financial Reports in Government Agencies (Study at the Department of Communication, Informatics and Statistics of Lampung Province) - khoirina, siti; rahmiati, siti (TECHNOBIZ : International Journal of Business, 2023)
This research was conducted at the Department of Communication, Informatics and Statistics, Lampung Province with the aim of empirically proving the effect of the Accounting Information System and Internal Control System simultaneously on the Quality of Financial Reports. The results of the analysis show that based on simultaneous testing using the F test, all research variables are Accounting Information Systems and Internal Control Systems. By looking at the influence of literacy, the calculated F value is 12,141. The F value of the table is 3.21 (the calculated F value is greater than the F table value) It can be concluded that the accounting information system (X1) and the internal control system (X2) where the simultaneous influence of X1 and X2 on Y is 0.000 < 0.00. It can be concluded that the value ( 0.000 < 0.05 ) means that the accounting information system (X1) and internal control system (X2) simultaneously affect the quality of financial reports (Y) at the Information Communications and Statistics Office of Lampung Province. Based on the partial test t-test accounting information system (X1) partially affects the quality of financial statements (Y) where the standard value tcount> ttable, tcount 3,576 > t table 1,680 and the internal control system (X2) partially also affects the quality of financial statements (Y), whose standard value is tcount >ttable , tcount 2,674 > t table 1,680. This means that the partial effect of X1 on Y is 0.001 < 0.05. It can be concluded that the significant value (0.001 <0.05) means that the accounting information system (X1) partially affects the quality of financial statements (Y) and X2 partially affects (Y) is 0.011 <0.05. It can be concluded that the significant value (0.011 <0.05) means that the accounting information system (X2) partially affects the quality of financial statements (Y)